Teaching research methodologies in professional training: an interdisciplinary dialogue between sociology and occupational therapy - Solsona Cisternas, Diego (My University, 2018)
The following article is presented as an effort to explain an educational experience in the exercise of teaching methodologies of research in a discipline pertaining to the health sciences as it is occupational therapy. The article attempts to explain the implications of teaching research methodologies when a teacher comes from related social science training and meets the challenge of adapting its collection of methodological knowledge to occupational therapy research problems. The author establishes similarities between the objects of study of sociology and occupational therapy, which at some point reach each other, in addition to identifying investigation levels (ontological, knowledge, epistemological and technical) to blend between the two disciplines. Finally it emphasizes the importance of identifying the pedagogical objectives when teaching methodologies and the need to talk intelligently with those from different social sciences disciplines.
Keywords: sociology; occupational therapy; research methodologies; pedagogical objectives; interdiscipline